Combustion related characterisation of Miscanthus peat blends applying novel fuel characterisation tools. (15th October 2015) - Sommersacher, Peter; Brunner, Thomas; Obernberger, Ingwald; Kienzl, Norbert; Kanzian, Werner
Highlights: Laboratory methods presented regarding the combustion related characterisation. Peat addition to Miscanthus increases the ash melting temperatures. Decreased aerosol emissions with increasing peat shares. Increased NO x and SO x emissions can be expected with increasing peat shares. New evaluation method for the prediction of optimum fuel blends for biomass fuels. Abstract: A continuously increasing demand for energy from biomass encourages utilisation of new biomass fuels which usually cause ash related problems in conventional wood combustion systems. One approach to make these biomass fuels applicable in such systems is to prepare blends with other fuels such as peat, which positively influence the behaviour of ash-forming elements. Usually the application of fuel blends has been evaluated experimentally, but in this study novel and advanced fuel characterisation tools (developed for fixed bed/grate combustion systems) are applied to Miscanthus/peat blends. In a first step the pure fuels and the Miscanthus/peat blends were chemically analysed. Fuel indexes provide primary information on ash-melting behaviour and a first estimation of the K release, indications of aerosol emissions, risk of high-temperature chlorine corrosion and the NO x emission potential. Thermodynamic equilibrium calculations were used for a qualitative and semi-quantitative prediction of the release of volatile and semi-volatile elements (K, Na, S, Cl, Zn, Pb) and the ash-melting behaviour. To quantitatively determine the release behaviour of ash-forming elements, lab-scale reactor experiments for the pure fuels and blends were conducted and a comparison with the theoretical calculations was performed. This work shows that the new approach of applying novel and advanced fuel characterisation tools to characterise Miscanthus/peat blends works well and meaningful blends can be recommended. The advantage of this characterisation method is that the influence of varying peat compositions (since the composition of peat strongly depends on its origin) can be considered. Additionally this approach helps to significantly reduce time-consuming and expensive testing programs.